A construção de uma tutela administrativa de elevado nível de proteção ao consumidor a partir das liberdades da pessoa na dinâmica tecno-humanista fundada nos direitos da privacidade e da proteção de dados - Horn, Luiz Fernando Del Rio (Universidade do Vale do Rio dos Sinos, 2018)
In the present thesis the qualitative changes in the consumption practice due to the recent technological waves have been verified, which are gradually compromising the freedoms of the consumer when of the electronic accesses invasive and invisible to the data of the singular person, revealing the predilections of purchase, determination of correlations, probabilities, and profile edits. Based on this new condition of subjection of the consumer, the following problem was mentioned: Considering the techno-humanist dynamics in contemporary times, how to promote, through public administration, a high level of consumer protection in Brazil, in order to guarantee the liberties of the person from two autonomous and interconnected rights, then transcribed in the rights of privacy and data protection? For that, the monographic method was adopted, having as methodological strategy the philosophical hermeneutics and the hermeneutic phenomenology guided by the transdiciplinary procedure for the composition of the macrodiscipline of deductive orientation. In order to ensure a foundation for questioning, the following hypotheses were raised: a first linked to the original revision of the temporal dimension of human existence to declare contemporaneity within a dynamic techno-humanist perception, transcribed in the duality of forces between techno (the technological apparatuses associated with instrumental rationality) and the social ethic of modern human rights. Another focused on the fundamentals of digital consumer protection, to predict the rights of privacy and data protection as autonomous, both raised in their objective dimensions, public administrative law and governed by positive tutelage, interconnected by the common interest of obtaining a greater consumer protection and guarantee of the freedoms of the person. Unpublished theoretical and applied contributions, confirmed during the course of the research and culminated in the creation of a set of actions of an administrative nature for the protection of the consumer, applicable to the Procons state network and extended to all SNDC, including electronic commerce, technical consumer products and the regime of unsolicited communications - border areas still pending absorption by law in order to increase the level of consumer protection.
Keywords: Tecno-humanismo; Sujeição do consumidor; Elevado nível de proteção; Privacidade; Dados; Techno-humanism; Consumer subjection; High level of protection; Privacy; Data; ACCNPQ::Ciências Sociais Aplicadas::Direito